Accidental archaeologist : memoirs of Jesse D. Jennings - Jennings, Jesse D. (Jesse David), 1909-1997 (University of Utah Press, 1994)
Few archaeologists have had as great an impact on American archaeology as Jesse Jennings. A founder of Great Basin archaeology, professor of anthropology for more than forty years, founder and director of the Utah Museum of Natural History, director of the Glen Canyon salvage team and such famous excavations as Danger, Hogup, and Cowboy caves, Jesse Jennings is a legend in the archaeological profession. Opinionated, rough-edged, direct, and insightful, Jennings takes readers from his youth in New Mexico, Baptist college, through graduate school at the University of Chicago in the '30s, early professional postings in the Southeast, the war years, work on the plains, Kaminaljuyu in Guatemala, and on to his lengthy tenure and influential work at the University of Utah as archaeologist and mentor. Jennings concludes his memoirs with a look at the current practice of archaeology.